Olfactory and neurological outcomes of SARS-CoV-2 from acute infection to recovery - Desai, Deesha D.; Yu, Sophie E.; Salvatore, Brock; Goldberg, Zoe; Bowers, Eve M. R.; Moore, John A.; Phan, BaDoi; Lee, Stella E. (Frontiers in Allergy, 2022)
Educational objective To investigate the impact of SARS-CoV-2 on sinonasal quality of life, olfaction, and cognition at different stages of viral infection and evaluate the association between olfaction and cognition in this population cohort. Objectives While olfactory dysfunction (OD) is a frequently reported symptom of COVID-19 (98% prevalence), neurocognitive symptoms are becoming more apparent as patients recover from infection. This study aims to address how different stages of infection [active infection (positive PCR test, symptomatic) vs. recovered (7 days post-symptoms)] compared to healthy control patients influence sinonasal quality of life, olfactory function, and cognition. Study design Prospective, longitudinal, case-control. Methods Participants completed the SNOT-22, University of Pennsylvania Smell Identification Test (UPSIT) and validated cognitive examinations to assess degree of smell loss and neurocognitive function at baseline and at 1 and 3 months for the active group and 3 months for the recovered group. Self-reported olfactory function and overall health metrics were also collected. Results The recovered group had the lowest average UPSIT score of 27.6 compared to 32.7 (active) and 32.6 (healthy control). 80% (n = 24) of the recovered patients and 56.3% (n = 9) of the active patients suffered from smell loss. In follow-up, the active group showed improvement in UPSIT scores while the recovered group scores worsened. In terms of neurocognitive performance, recovered patients had lower processing speed despite an improving UPSIT score. Conclusion SARS-CoV-2 infection was found to impact olfactory function in a delayed fashion with significant impact despite recovery from active infection. Although olfactory function improved, decrements in cognitive processing speed were detected in our cohort.